Gastric Crohn disease in children. - Benedictti, Juan L; Sbárbaro, Orestes; Sojo, Enrique; Falconi, Luis (Cirugía del Uruguay, 1984)
Description of a case of gastric Crohn disease in a 13-years-old-girl. Crohn disease is in fact no very frequent, this one being the first case described locally, concerning a child and with a gastric topographic location. Authors consider clinical, radiological and endoscopic aspects of the case, also considering the thera• peutic behavior of same.